Agricultural and natural resource data bank for Thailand - Jintana Gajadesa; Kanchit Malaivongs; Huynh, Ngoc Phien; Gonzales, Jr. R. L.; USAID/AID (Bangkok : Asian Institute of Technology, 1984)
This study presents the analysis, design and partial implementation of a computerized Agricultural and Natural Resource Data Bank System (ANRDBS) for the Ministry of Agriculture and Cooperatives (MOAC). The current operation of the system was studied and requirement for the proposed system were specified. these are used in establishing the necessary objectives processing requirements of the ANRDBS to include systematic information gathering, processing, storing and dissemination. A partial implementation emphasizes on gathering, processing and storing of plant information. The system uses MAPPER package with retrieval, inquiry and report generation capabilities, implemented on UNIVAC 1100/60, for file creation, access and coding the programs. This package is based on the relational model. The system also uses six kinds of plants as examples. The same system concept can be extended to cover other types of agricultural information.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1984
Keywords: Natural resources -- Thailand -- Data processing; Agriculture -- Thailand -- Data processing